1992
DOI: 10.1002/gcc.2870050210
|View full text |Cite
|
Sign up to set email alerts
|

Translocation t(11; 14)(q 13;q32) in chronic lymphoid disorders

Abstract: The translocation t(11;14)(q13;q32) has been described in a spectrum of B-lymphoproliferative diseases and involves a putative oncogene, BCL1, which maps to chromosome band 11q13. Recent evidence indicates that this abnormality may delineate particular subtypes of lymphoma, such as intermediate lymphocytic and centrocytic lymphomas. Thus the possible significance of the t(11;14) within B-cell disorders should be reexamined in the light of a more objective approach to classifying these diseases by morphology, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…[42][43][44] This feature is considered to be characteristic of MCL although it can also be seen in plasma-cell leukemia, multiple myeloma, hairy cell leukemias, and B-prolymphocytic leukemia, 45 and is missing in MCL. 7,46 We have demonstrated that the cyclin D1 signature was a feature independent from the MCL signature.…”
Section: Sll Splenic Mzl and MCL Lymphomas Display Specific Genomicmentioning
confidence: 99%
“…[42][43][44] This feature is considered to be characteristic of MCL although it can also be seen in plasma-cell leukemia, multiple myeloma, hairy cell leukemias, and B-prolymphocytic leukemia, 45 and is missing in MCL. 7,46 We have demonstrated that the cyclin D1 signature was a feature independent from the MCL signature.…”
Section: Sll Splenic Mzl and MCL Lymphomas Display Specific Genomicmentioning
confidence: 99%
“…In the literature these cases have variously been called MCL, mantle cell leukemia, atypical CLL, PLL, and splenic lymphoma with villous lymphocytes (SLVL). [13][14][15][16][17] The basic question as to whether all cases with t(11;14) circulating lymphocytes are MCL variants or whether they encompass other diseases is unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Follicular lymphoma carries the t(14;18)(q32;q21) in more than 80% of cases whilst 50-70% of mantle-cell lymphoma (MCL), [1][2][3][4][5] cases of splenic lymphoma with villous lymphocytes (SLVL) and lymphoplasmacytic lymphomas [6][7][8][9] have the t(11;14)(q13;q32) involving the IgH gene locus and the BCL1/cyclin D1 gene. In addition, few reports have suggested that t(11;14) is present in rare cases of atypical CLL although some of these patients have clinical and/or laboratory features of MCL.…”
Section: Introductionmentioning
confidence: 99%